2014
DOI: 10.4103/0972-3919.125776
|View full text |Cite
|
Sign up to set email alerts
|

A case of VACTERL and non-VACTERL association without the "V and L"

Abstract: VACTERL is a cluster of congenital malformations based on the non-random association of various congenital malformations in a single patient. Here “V” denotes vertebral defects or vascular anomalies (single umbilical artery), “A” anal atresia, “C” cardiac abnormalities, “TE” tracheoesophageal fistula, “R"renal (kidney) abnormalities and “L” for limb anomalies) It is called an association, rather than a syndrome because the complications are not pathogenetically related, tend to occur more frequently than expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Reports have shown that newborns with VACTERL association and ipsilateral renal disorders have the same side limb defects [14]. This contracts with our case who had bilateral affectation of the kidneys and unilateral affectation of the left lower limb.…”
Section: Discussionsupporting
confidence: 88%
“…Reports have shown that newborns with VACTERL association and ipsilateral renal disorders have the same side limb defects [14]. This contracts with our case who had bilateral affectation of the kidneys and unilateral affectation of the left lower limb.…”
Section: Discussionsupporting
confidence: 88%
“…The diagnosis of VACTERL association can only be confirmed once at least 3 of the above-mentioned congenital malformations are identified in a patient [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] The etiology is thought to be embryologically related. [ 8 ] Management usually depends on correcting specific congenital anomalies immediately after birth, followed by long-term medical management of any sequelae resulting from the congenital malformations. Although genital defects—are not the major defect of VACTERL association, in a study by Botto et al of 286 infants with Vertebral anomalies, anal atresia, tracheoesophageal fistula, renal dysplasia, and limb abnormalities (VATERL) association, 81 (28.3%) had severe genital defects.…”
Section: Introductionmentioning
confidence: 99%